Woven Eutectic Lamellar Structures Lead to Ultrahigh Strength and Energy Absorption Capacity in Additively Manufactured Lattice Structures - Zhiyong Ji; Xingyu Pan; Longlong Wang; Xintian Wang; Xu Chen; Hanwei Fu; Chunlei Qiu (Small Structures)
In this study, a high‐strength eutectic high‐entropy alloy, AlCoCrFeNi2.1, is selected to produce lattice structures by selective laser melting to achieve high strength, good damage tolerance, and strong energy absorption capacity. The as‐printed lattice struts are found to contain numerous colonies of nanosized eutectic lamellar structures which are curved and interwind with each other to form a woven microstructure. The unique microstructure leads to unprecedented effective metal strength, yield strength, normalized strength, and specific energy absorption (SEA) for the lattice structures. The face‐centered cubic nanolamellae undergo more extensive plastic deformation by forming a higher density of dislocations and stacking faults than the body‐centered cubic lamellae, leading to excellent ductility and SEA. The heterogeneous deformation between the two phases may generate large local plastic strain gradients leading to strong back‐stress hardening. The ultrafine eutectic colonies together with the high density of colony boundaries are not only good for strength but also beneficial to damage tolerance because they can effectively deflect crack propagation path. The type of lattice structure affects the mechanical properties to a certain extent by changing the internal stress and strain distribution within struts and the global deformation and fracture modes of the lattice structures.